PENGARUH LIKUIDITAS, PROFITABILITAS, DAN LEVERAGE TERHADAP HARGA SAHAM PADA PERUSAHAAN PERDAGANGAN BESAR YANG TERDAFTAR PADA BURSA EFEK INDONESIA (BEI) PERIODE 2018-2020 - Ranni Putri Ananda; Seflidiana Roza; Nurhayati, Nurhayati (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
Stock prices are prices that occur on the stock market at a certain time determined by market participants and determined by the demand and supply of the shares concerned in the capital market. The share price is the present value of the income that will be received by investors in the future. Stock prices can change up and down in a matter of time so quickly. The purpose of this study was to determine the effect of liquidity, profitability and leverage on stock prices. The object of this study is a large trading company listed on the Indonesia Stock Exchange (IDX) as many as 20 samples of companies obtained after using a sampling technique, namely purposive sampling. The type of data in this study is quantitative. Sources of data used are secondary data derived from the company's financial statements for a period of 3 years. Based on the results of the multiple linear regression analysis carried out, it was obtained that Y= 7,447 – 0,045X1 + 0,036X2 - 0,219X3 + e This means that liquidity has a significant negative (-) effect on stock prices, profitability has a significant positive (+) effect on prices. stocks and leverage have a negative (-) effect on stock prices. The results of the f test obtained that the fcalculated is 5,436 >ftable 2.79 means that liquidity, profitability, and leverage have a significant effect on stock prices in large trading companies listed on the IDX.